O culto à Oxorongá nos templos de candomblé: um fenômeno contemporâneo na cidade do Recife - Gomes, Andréa Caselli (2015)
This paper proposes a focus on the recent change in the forms of candomblé houses religion in the metropolitan region of Recife: the cult of Iami, female entities present in the Yoruba mitology. Since the beginning of the XXI century; worship, originally secret and exclusively female ancestors to entities designated as Iami, has been controversial and divisive issue among fans of african-brazilian religions, especially among those seeking reafricanization in their religious experiences. In Pernambuco there are temples and cult followers who carry this deliberately, often without knowing their deep traditional roots; observed contemporary rescue of an activity that has long lost its original meaning, since the new practices entail recent elaborations of myth and ritual on the feminine aspect. Such activity has been adopted and exploited by male fans; they are responsible for the recent popularity of the cult, especially among young fans. The methodological tools used were the historical literature on the topic, the literature legends and myths collected by ethnographers and references by authors from the fields of anthropology, history, and psychology; to ensure that the research has transdisciplinary nature and promotes interfaith dialogue. The material was systematized in a theoretical framework grounded in conceptions of the anthropologist Gilbert Durand about imaginary anthropologist Nestor Garcia Canclini's about cultural hybridity and anthropologist Pierre Verger of Yoruba ancestry. Through qualitative research, were verified sources and influences that resulted in this phenomenon, and also the social factors that led to its emergence and its rapid expansion, including the rescue of female ax and the formation of new identities in African- Brazilian religion a postmodern context of rapid transformation.